Isolation of Coliphage from Fewa Lake - Adhikari, Subash (Janapriya Journal of Interdisciplinary Studies, 2017)
Bacteriophages are host specific viruses targeting only certain types of bacteria. Bacteriophages infecting E-coli are called coliphages. The suspension was prepared from water and tested for the presence of phage. Isolation of bacteriophage by infecting host and experiment isolate coliphage from 45ml water from Fewa Lake by introducing them to 24hrs old culture of E-coli followed with centrifugation and filtration. This study was conducted to study virus-bacteria relationship and if phage could be used to remove fecal coliform from Fewa lake. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 96-100